The art of nonverbal communication: Emoji / Efina Hamdan ... [et al.] - Hamdan, Efina; Mior Kamarulbaid, Afiqah; Mohd Shukri, Nur Alyani; Ramli, Noryusnita; Abdullah, Nur Fadzilah (2022)
Communication is key. A common phrase we always hear when relationship is the subject of conversation. Many of us believe that communication helps building, enhancing and sustaining relationships between people. We humans communicate to deliver messages, to express feelings and emotions as well as to share some ideas or information with others. As much as communication being essential to human being, comprehension is important too. The ultimate goal of communication is for the other person to understand and perceive the messages as what and how we wish them to. When receivers are able to understand and comprehend the message sent, we can happily say that our communication objective is achieved.